Characteristics of Antibiotic Prophylaxis and Risk of Surgical Site Infections in Open Colectomies. Issue 8 (August 2016) - Poeran, Jashvant; Wasserman, Isaac; Zubizarreta, Nicole; Mazumdar, Madhu
Abstract : BACKGROUND: Despite numerous trials assessing optimal antibiotic prophylaxis strategies for colorectal surgery, few studies have assessed real-world practice on a national scale with respect to risk of surgical site infections. OBJECTIVE: Using a large national claims database we aimed to describe current use of prophylactic antibiotics (type and duration) and associations with surgical site infection after open colectomies. DESIGN: This was a retrospective study using the Premier Perspective database. SETTINGS: Included were patient hospitalizations nationwide from January 2006 to December 2013. PATIENTS: A total of 90, 725 patients who underwent an open colectomy in 445 different hospitals were included in the study. MAIN OUTCOME MEASURES: Multilevel, multivariable logistic regressions measured associations between surgical site infection and type of antibiotic used and duration (day of surgery only, day of surgery and the day after, and >1 day after surgery). RESULTS: Overall surgical site infection prevalence was 5.2% (n = 4750). Most patients (41.8%) received cefoxitin for prophylaxis; other choices were ertapenem (18.2%), cefotetan (10.3%), metronidazole with cefazolin (9.9%), and ampicillin with sulbactam (7.6%), whereas 12.2% received other antibiotics. Distribution of prophylaxis duration was 51.6%, 28.5%, and 19.9% for day of surgery only, day of surgery and the day after, and >1 day after surgery, respectively. Compared with cefoxitin, lower odds for surgical site infection were observed for ampicillin with sulbactam (OR = 0.71 (95% CI, 0.63–0.82)), ertapenem (OR = 0.65 (95% CI, 0.58–0.71)), metronidazole with cefazolin (OR = 0.56 (95% CI, 0.49–0.64)), and "other" (OR = 0.81 (95% CI, 0.73–0.90)); duration was not significantly associated with altered odds for surgical site infection. Sensitivity analyses supported the main findings. LIMITATIONS: The study was limited by its lack of detailed clinical information in the billing data set used. CONCLUSIONS: In this national study assessing real-world use of prophylactic antibiotics in open colectomies, the type of antibiotic used appeared to be associated with up to 44% decreased odds for surgical site infections. Although there are numerous trials on optimal prophylactic strategies, studies that particularly focus on factors that influence the choice of prophylactic antibiotic might provide insights into ways of reducing the burden of surgical site infections in colorectal surgeries.